Probabilistic analysis of a table tennis game - Noubary, R. D. (Journal of Quantitative Analysis in Sports, 2007)
A game of table tennis is analyzed using elementary concepts of calculus, probability, and linear algebra. The analysis includes modeling using different approaches and a comparison of the results obtained under the new and the old rules for the game. The analysis demonstrates the steps of a mathematic modeling and illustrates the possible expansion of it.